Immunosenescence and metabolic reprogramming in MASLD: an age-dependent immunometabolic vicious cycle and therapeutic opportunities - Xu, Yuxin; Li, Qiuxiang; Jiao, Xuehua (Frontiers in Cell and Developmental Biology, 2025)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) poses a disproportionately severe burden on the aging population, with a heightened risk of progression to advanced fibrosis and cancer. While immunosenescence and metabolic reprogramming are recognized as key drivers, this review proposes an age-dependent immunometabolic vicious cycle as a critical integrative framework underlying MASLD progression. We hypothesize that at the core of this cycle lies mitochondrial dysfunction and reactive oxygen species (ROS) accumulation, which may initiate a self-amplifying loop: triggering NLRP3 inflammasome activation in Kupffer cells, promoting a context-dependent dysfunction of adaptive immunity. This includes driving CD8+ T cells toward exhaustion in advanced disease and disrupting regulatory T cell (Treg) function, which may range from loss of suppressive capacity to a pro-fibrotic phenotypic switch. Together, these alterations in T cell immunity create a permissive environment for unchecked inflammation and fibrosis. This cycle is further reinforced by gut-liver axis dysfunction. Critically, this framework reveals that overcoming the therapeutic bottleneck in age-associated MASLD necessitates a paradigm shift toward combination therapies that simultaneously target multiple nodes of the cycle.